ITIL Foundation Essentials ITIL 4 Edition - The ultimate revision guide, second edition - Agutter, Claire (IT Governance Publishing, 2020)
ITIL® Foundation Essentials ITIL 4 Edition is the ultimate revision guide for candidates preparing for the ITIL 4 Foundation exam. It is fully aligned with the Foundation course syllabus and gives a clear and concise overview of the facts. This second edition has been updated to align with amendments to the ITIL® 4 Foundation syllabus.
Title from content provider
Keywords: Libros electrónicos; Diseño estructural; Servicios de información